Factors associated with lipid control in outpatients with heart failure - Jarab, Anan S.; Al-Qerem, Walid; Hamam, Hanan; Abu Heshmeh, Shrouq; Mukattash, Tareq L.; Alefishat, Eman A. (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background: Dyslipidemia is common among patients with heart failure, and it negatively impacts clinical outcomes. Limited data regarding the factors associated with poor lipid control in patients with HF patients. Therefore, this study aimed to evaluate lipid control and to explore the factors associated with poor lipid control in patients with HF. Methods: The current cross-sectional study was conducted at outpatient cardiology clinics at two major hospitals in Jordan. Variables including socio-demographics, biomedical variables, in addition to disease and medication characteristics were collected using medical records and custom-designed questionnaire. Medication adherence was assessed using the validated 4-item Medication Adherence Scale. Binary logistic regression analysis was conducted to explore significant and independent predictors of poor lipid control among the study participants. Results: A total of 428 HF patients participated in the study. Results showed that 78% of the participants had poor lipid control. The predictors that were associated with poor lipid control included uncontrolled BP (OR= 0.552; 95%CI: 0.330-0.923; P<0.05), higher Hb levels (OR= 1.178; 95%CI: 1.013-1.369; P<0.05), and higher WBC (OR= 1.133; 95%CI: 1.031-1.246; P<0.05). Conclusions: This study revealed poor lipid control among patients with HF. Future intervention programs should focus on blood pressure control in order to improve health outcomes among HF patients with dyslipidemia.